Language and Aging Research in Open Science platforms - Bowie, David; Gerstenberg, Annette (Journal of Language and Aging Research, 2024)
Open Science is not just a rewarding endeavor for those involved in Language and Aging Research (LAR), but an important pursuit in its own right. The editorial presents two Open Science platforms and asks whether and how LAR topics are addressed. The transmission of academic knowledge to a wider public of practitioners, older adults and their environment could potentially improve the daily challenges of family life and care settings. Beyond this unidirectional transmission, the presence of a wider public and the awareness of channels to spread the knowledge can also inspire research and help to focus on relevant topics suitable for applications in real world scenarios.